Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kepuasan Kerja Pegawai di Dinas Pertanian Kabupaten Bima - Muh. Rizki; Muhammad Yusuf; Julaiha Julaiha (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the effect of organizational culture and work discipline on employee job satisfaction at the Department of Agriculture of Bima Regency, both partially and simultaneously. This research employed a quantitative approach with an associative research design. The population consisted of 100 employees, while the sample comprised 45 civil servants selected using a purposive sampling technique. Data were collected through observation, questionnaires, and literature review. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, t-test, and F-test with the assistance of SPSS. The results showed that organizational culture had a positive and significant effect on employee job satisfaction (t = 2.246; Sig. = 0.030), work discipline had a positive and significant effect on employee job satisfaction (t = 6.864; Sig. = 0.000), and organizational culture and work discipline simultaneously had a significant effect on employee job satisfaction (F = 52.975; Sig. = 0.000). The coefficient of determination (R²) was 0.716, indicating that 71.6% of the variation in employee job satisfaction could be explained by organizational culture and work discipline, while the remaining 28.4% was influenced by other factors outside the scope of this study.